(untitled) (Annals of Medical Research, 2021)
Aim: The goal of the present study was to investigate the effects of 17-alpha-hydroxyprogesterone caproate (17-OHPC) on oral glucose tolerance test (75 g OGTT) results and the prevalence of gestational diabetes mellitus (GDM). Material and Methods: : In the present case-control study, 1,472 pregnant women were enrolled. Of these pregnant women, 146 had used 17-OHPC for at least one month between 16–24 weeks of gestation and the remaining 1,326 were the healthy control group. Diagnostic criteria presented by International Association of Diabetes and Pregnancy Study Group were applied for diagnosis GDM.Results: Maternal demographic characteristics were similar between groups. The mean starvation serum glucose level was importantly greater in the study group at 81.7 ± 9.3mg/dL versus 79.6 ± 13.3mg/dL in the control group. Mean first hour serum glucose was 144.4 ± 30.4mg/dl in the study group and 130.8 ± 36.9mg/dl in the control group, importantly greater in the study group. Mean second hour serum glucose was importantly greater in the study group at 111.5 ± 26.1mg/dl versus 104.8 ± 31.4mg/dl in the control group. Additionally, there was no statistically significant difference between the groups for GDM prevalence.Conclusion: The present study showed that 17-OHPC was importantly related to greater starvation, first hour, and second hour serum glucose levels compared with the healthy group.